2023
DOI: 10.3126/ajms.v14i2.49128
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of automated cell counter RBC histograms and peripheral smear in anemia typing

Abstract: Background: Red blood cell (RBC) indices and histogram obtained from automated hematology gives an idea about the morphological changes in anemia and therefore forms the fundamental process for diagnosis of anemia. Along with the peripheral smear, they can be used for anemia typing and to interpret the cause of anemia. Aims and Objectives: (1) Interpretation of histograms in normal persons and patients with different types of anemia. (2) Anemia typing based on RBC histograms complemented with Peripheral smear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…14 In our study, RBC histogram showed normal curve in (53.0%) cases, Left shift in (37.6%) cases, Right shift (2%) cases, Bimodal (2%) cases, and Broad base (5.4%) cases and these findings correlated with previous studies (►Table 3). [16][17][18] Among 500 cases, peripheral smear examination and interpretation were done for all the cases in our study. In our study, it was observed that on peripheral smear study, normocytic normochromic anemia (54.4%) was the most common type followed by microcytic hypochromic anemia, macrocytic anemia, and dimorphic anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In our study, RBC histogram showed normal curve in (53.0%) cases, Left shift in (37.6%) cases, Right shift (2%) cases, Bimodal (2%) cases, and Broad base (5.4%) cases and these findings correlated with previous studies (►Table 3). [16][17][18] Among 500 cases, peripheral smear examination and interpretation were done for all the cases in our study. In our study, it was observed that on peripheral smear study, normocytic normochromic anemia (54.4%) was the most common type followed by microcytic hypochromic anemia, macrocytic anemia, and dimorphic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, RBC histogram showed normal curve in (53.0%) cases, Left shift in (37.6%) cases, Right shift (2%) cases, Bimodal (2%) cases, and Broad base (5.4%) cases and these findings correlated with previous studies ( Table 3 ). 16 17 18…”
Section: Discussionmentioning
confidence: 99%